2018
DOI: 10.1242/jeb.165696
|View full text |Cite
|
Sign up to set email alerts
|

Environmental acoustic cues guide the biosonar attention of a highly specialised echolocator

Abstract: Sensory systems experience a trade-off between maximizing the detail and amount of sampled information. This trade-off is particularly pronounced in sensory systems that are highly specialised for a single task and thus experience limitations in other tasks. We hypothesised that combining sensory input from multiple streams of information may resolve this trade-off and improve detection and sensing reliability. Specifically, we predicted that perceptive limitations experienced by animals reliant on specialised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…in the range of the sonar beam directionality or even narrower. More data on hearing directionality, hearing direction, their variation due to ear movements (e.g., Griffin et al 1962;Kugler et al 2017, Lattenkamp et al 2018, Yin & Mülller 2019, and on natural scanning behaviour will be required to estimate the average prey detection cone of free-flying bats.…”
Section: Neural Representation Of Predator Threat Page 24mentioning
confidence: 99%
“…in the range of the sonar beam directionality or even narrower. More data on hearing directionality, hearing direction, their variation due to ear movements (e.g., Griffin et al 1962;Kugler et al 2017, Lattenkamp et al 2018, Yin & Mülller 2019, and on natural scanning behaviour will be required to estimate the average prey detection cone of free-flying bats.…”
Section: Neural Representation Of Predator Threat Page 24mentioning
confidence: 99%
“…Bats targeting the fluttering sounds of moths are not surprising given the nocturnal habits of both groups; indeed, many bat species exploit this sensory strategy (e.g., Myotis septentrionalis , Myotis lucifugus [Ratcliffe & Dawson, ]; Myotis evotis [Faure & Barclay, ]; Plecotus auritus [Anderson & Racey, , ]). Even bats with highly specialized neurological and morphological adaptations to use echolocation to detect fluttering moths also attend to the sounds produced by moth movements, underlying the importance of simply listening for prey‐emitted locomotion cues (e.g., Rhinolophus ferrumequinum , Lattenkamp et al, ).…”
Section: Private Information Usementioning
confidence: 99%
“…Phylogeny adapted from Kaňuch, Aghová, Meheretu, Šumbera, and Bryja (), Roehrs, Lack, and Bussche (), Rojas, Warsi, and Dávalos () and Stadelmann, Lin, Kunz, and Ruedi (). References for prey cue and signal use by bat species: 1 Lattenkamp et al (); 2 Raghuram et al (); 3 Ryan and Tuttle (); 4 Fiedler (); 5 Marimuthu and Neuweiler (); 6 Marimuthu et al (); 7 Fenton et al (); 8 Bell (); 9 Vehrencamp, Stiles, and Bradbury (); 10 Schmidt et al (); 11 Gröger and Wiegrebe (); 12 Heffner et al (); 13 Jones et al (); 14 Bell (), 15 Fuzessery et al (); 16 Holderied et al (); 17 Anderson and Racey (); 18 Anderson and Racey (); 19 Coles et al (2004); 20 Siemers et al (); 21 Jones et al (); 22 Arlettaz et al (); 23 Faure and Barclay (); 24 Ratcliffe and Dawson (); 25 ter Hofstede, Ratcliffe, and Fullard (); 26 Alem et al (); 27 Belwood and Morris () (note that in this study, Micronycteris microtis is referred to as Micronycteris megalotis and Lophostoma silvicolum as Tonatia silvicola , reflecting the phylogenetic understanding at the time); 28 Falk et al (); 29 Page and Jones (); 30 Patriquin et al (); 31 Bailey and Haythornthwaite (); 32 Buchler and Childs ()…”
Section: Private Information Usementioning
confidence: 99%
“…Previous studies on a range of behaviors have demonstrated how terrestrial and aquatic animals utilize and integrate multiple cue modalities (e.g. Dusenbery, 1992;Pluta and Kawasaki, 2008;Harley et al, 2011;Igulu et al, 2013;Ravi et al, 2016;Lattenkamp et al, 2018), and specifically how cue hierarchies can lead to optimal decisions in dynamic marine environments (e.g. Kingsford et al, 2002;Woodson et al, 2007;Fuchs et al, 2010;Seuront, 2013).…”
Section: Sensing the Shoreline: Cue Hierarchies And Reversible Versusmentioning
confidence: 99%